New Blue Light Emissive Polyazomethine(S) Containing Bromo-Triphenyl Units: Synthesis and Photophysics. Issue 4 (4th March 2019) - Khalid, Naila; Bibi, Ahtaram; Akhtar, Khalida; Mustafa, Kashif; Khan, Mussabeha; Saeed, Nishat
ABSTRACT: A series of bromo-substituted triphenylamine based poly(azomethine)s (P1-P3) were synthesized from the N 1 -(4-aminophenyl)- N 1 -(4-bromophenyl)benzene-1, 4-diamine (DA) and aromatic dialdehydes. The viscosity of P1-P3 solutions (0.97 to 1.12 g dL −1 ) and molecular weight distribution analysis by Gel Permeation Chromatography (GPC) discloses the attainment of appreciable molecular weight. The optical transparency and fluorescence properties of the P1-P3 were explored by UV- vis and photoluminescence spectral analysis. From which it was concluded that the presence of 4-bromotriphenylamine and azomethine (CH = N) linkage in our synthesized materials are possibly responsible for the fluorescence with quantum efficiencies of 0.9–2.1 %. GRAPHICAL ABSTRACT: